The Life of Hedonism from the Perspective of Al-Tabari and Sayyid Muhammad Rashid Rida (Comparative Study of Tafsir Surah Ali Imran: 14) - Mohammad Fattah; Sri Ardila (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Qur'an not only tells us about prohibitions and commands, but also talks about the problems of the lives of previous people. Among them are illustrated by the human lifestyle that prioritizes pleasure and physical luxury. Based on the hedonistic lifestyle, it certainly has 'ibrah that can be learned if an in-depth study of the life of hedonism is carried out. The author wants to examine the life of hedonism from the perspective of al-Tabari and Sayyid Muhammad Rasyid Rida. This paper uses a qualitative approach that is classified into library research with library materials, especially Jami' al-Bayan fi Ta'wil Ayi al-Qur'an and Tafsir al-Manar and uses comparative data analysis. The conclusion in this paper is that the life of hedonism according to al-Tabari and Sayyid Muhammad Rasyid Rida is an excessive human lifestyle and indulges in lust in reaching the pleasures of the world. The similarities and differences according to these two mufassirs are almost the same in interpreting the life of hedonism in surah Ali Imran verse 14 that Allah SWT makes beautiful in human views of the pleasures of the world, namely women, children, large assets of gold and silver, selected horses, livestock and rice fields. Sayyid Muhammad Rasyid Rida besides agreeing with Imam al-Tabari, he added that human love for the beauty and pleasure of the world is not only specific to the Jews, but is general.